INSTRUMENTS AND SCOPE OF MONETARY POLICY IN LIBYA - الحاسية ميلود (Dirasat in Economics and Business, 1975)
In this paper we discuss the major implications of the structure of the monetary and financial sector in Libya on the application and effectiveness of the different monetary and financial instruments to affect money and credit in the economy. By examining the various financial ratios in the Libyan economy, we have concluded that the financial-monetary sector has not achieved much financial deepening during the period of 1958-75, in spite of the tremendous growth in all monetary and financial variables in absolute terms, Another important aspect of the monetary sector is the existence of a very limited financial market. The absolute number of buyers and sellers is few, and hence the maximum average frequency of transactions is very low.